Effect of Operation Neptune Spear on Anti-Americanism in Mainstream Pakistani Press - Rawan, Bakht (The Journal of Humanities & Social Sciences, 2023)
This study analyses anti-Americanism in the mainstream press of Pakistan before and after the Operation Neptune Spear (ONS) also called Abbottabad Operation conducted by US forces in Abbottabad (Pakistan) in which Osama bin Laden (OBL) was killed. The researcher analysed coverage of drone attacks and Abbottabad Operation in op-ed pages of four leading national newspapers i.e., Dawn, The News, Nawa-i-Waqt, and Express. Total time of the study was four months, two months before the Operation (01 March 2011 to 30 April 2011) and two months after the Operation (01 May 2011 to 30 June 2011). The ONS was taken as an independent variable for exploring anti-Americanism in the mainstream Pakistani media (print media) while “drone attacks” was taken as a control variable. Anti-Americanism in op-ed pages of the selected newspapers was compared to determine the effect of ONS on anti-Americanism in the mainstream Urdu and English press of Pakistan. The results revealed that US image in the Pakistani press remained negative throughout the study period and the ONS had no significant effect on the image of USA in Pakistani leading press.